Discrimination between nearby and direct lightning strikes to a long operational medium voltage line to assist in the determination of the basic insulation level (BIL) - Van Schalkwyk, Willem Jacobus Dirkse (University of the Witwatersrand, Johannesburg, 2022)
The lightning performance of a Medium Voltage (MV) line needs to be divided into two categories: lightning performance due to nearby lightning and direct lightning strikes. A better nearby lightning performance requires a higher Basic Insulation Level (BIL) while the direct lightning performance requires a lower BIL to minimize equipment failure. The electromagnetic coupling models for calculating the Lightning Induced Overvoltage (LIOV) on a line are complicated and reliant on accurate input data. Therefore, short floating lines (< 3 km) were used to calculate the line’s lightning performance. The models were then verified with LIOV measurements on these short floating lines and the results were normalized to estimate the lightning performance of long operational lines. These estimations for long lines could never be verified due to the complexity of calculations and the cost and logistics of equipment to do measurements on long operational lines. A new methodology to measure the lightning performance of a long operational line was developed and verified. The obstacles such as the long line length, the changing soil resistivity, the lightning channel properties and the rapid attenuation of the LIOV along the energized line have been used as an advantage in the new method. The finite soil conductivity was used as an advantage to distinguish between nearby lightning and direct lightning strikes while the power frequency current was used to determine whether the LIOV exceeded the line BIL and caused a line fault. An existing electromagnetic coupling computer model, the ATP-EMTP, was verified with the existing ERM using the same input data. The ATP-EMTP model was then extended to include the equipped long MV line. There was no existing model or measurements to which the results could be compared to. Actual nearby lightning and direct lightning strikes of which the termination point was known were used to verify the new methodology. A significant size database (consisting of 38 675 lightning flashes and 1 155 line faults over two years) was used to evaluate the IEEE Std 1410-2010 estimated lightning performance of the long line.
A thesis submitted in partial fulfilment of the requirements for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2022
Keywords: Direct lightning; Lightning performance; Medium Voltage (MV) line; Basic Insulation Level (BIL); Lightning Induced Overvoltage (LIOV); UCTD